Elisabeth Mann Borgese and the Law of the Sea - Meyer, Tirza (Legal History Library, 2022)
This book explores how ocean governance expert Elisabeth Mann Borgese (1918-2002) spent decades fighting to promote her radical vision of a just ocean order in the United Nations Law of the Sea Convention.